The Interest of the People of South Kalimantan in Practicing and Developing Pickleball - Lazuardy Akbar Fauzan; Sofyan; Nadia Salasabila; Muhammad Faisal; Ma’ruful Kahri Kahri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Pickleball is a new sport. In South Kalimantan there are IPF management in 10 Regencies and Cities. The task of each management is to increase interest in pickleball participation at the regional level and explore the potential of talented athletes. The IPF management as a whole has not been active in socializing pickleball in the general public. We only meet this sport quite actively in a few areas. The aim of this study . This research is a descriptive quantitative research. The variable studied in this study is the development of community interest in pickleball. Data collection techniques using instruments in the form of questionnaires and interviews. The population and sample of this study are all branch management at the city and district levels in South Kalimantan. The sampling technique used is total sampling. This study used an instrument with a Likert scale with 5 answer choices. The data analysis used is descriptive statistics. The results of this study showed that from the intrinsic elements there were as many as 37.8% strongly agree and 34.9% agreed stating that the success of pickleball to be able to develop must come from one's own will first. There are extrinsic elements as much as 22.7% strongly agree and 24.8% agree that for the success of pickleball to be able to develop there must be support from outsiders themselves.